Bibliometric Study of TVET and Industry Synergies in the Digital Era on Global Research Direction and Strategy - Aura Salsabillah Rahmatya; Suprih Widodo; Ulva Elviani (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2025)
This study aims to assess the direction and strategy of global research related to the synergy between vocational education and training (TVET) and industrial needs in the digital era through a bibliometric approach. The analysis was conducted on 500 scientific documents obtained from the Scopus database using VOSviewer and Biblioshiny software. The analysis showed that keywords such as higher education, vocational education, workplace learning, innovation, employability, and industry 4.0 dominated the scientific discourse, signalling the important role of TVET in building employability skills based on digital industry needs. The thematic visualisation identified four main clusters in the research: (1) education and training, (2) digitalisation and innovation, (3) outcome orientation such as entrepreneurship and employability, and (4) sustainable development and well-being. Geographically, countries such as Germany, Australia, Malaysia, China, Indonesia, South Africa, and Nigeria emerged as major contributors with varied research focuses. Highlighted global strategies include revitalising TVET curricula, strengthening, triple helix collaboration (academic, industry, government), enhancing employability skills through work-based learning approaches, and digitalising learning processes. The findings provide a useful conceptual mapping for stakeholders in developing adaptive, collaborative, and sustainable vocational education policies and practies in the digital era.